Penerapan Konsep Arsitektur Tropis Pada Perancangan Perumahan di Banda Aceh - Ravi Sharni; Irzaidi Irzaidi; Mirza Mahmud (Universitas Syiah Kuala, 2022)
Abstract The ever-growing population is a major factor in the problem of rapid increase in population unequal to the provision of housing. To meet demand for living quarters in the region of banda aceh and to improve the welfare of city population banda aceh. From this assumption, it suggests that a study of residence planning for the people of banda aceh in particular in the form of